PENGARUH TEKNIK PERBAIKAN TEGAKAN RUMPUN TERHADAP PENINGKATAN PRODUKTIVITAS BATANG BAMBU TALI (Gigantochloa apus KURZ.) (The effect of repairing technique to clumps stand to the culm productivities of bambu tali (Gigantochloa apus Kurz) ) - sutiyono sutiyono; yamin mile; marfu'ah wardani (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2011)
ABSTRACT   Bambu tali (Gigantochloa apus Kurz.) known as bambu species that used many for handicraft materials. But their clump existence often damage without tending and many cutting remainder  the research of repairing technique of clump to improve the productivity of culms have been done in forest research station Balai Penelitian Kehutanan Ciamis for 2 years from 2009 to 2010. The research were arranged according to RCBD (Random completely block design) consist of three treatments that are : A. Clump repaired total, all cutting remainder were removed, B. Clump repaired apart, half of cutting remainder were removed,  C. Clump without repaired, as control. Every treatment consist of  seven  replications and the data collection includes of the amount of culm/clump, clump circumference, clump density, culm high and culm diameter. Data collecting done in the intial and one year after treatment. All data were analyzed by the  analysis of variance. Result of research showed that clump repaired total (A) can improve the amount of culm/clump of  116,2% bigger compared to clump repaired apart (B) which only 67,3% and or again clump without repairing (C)  which 50,3%. Beside that, clump reapiring total (A) can improve the culm height of 107,3% bigger compared to clump repaired (B) which of 101,6% or and the clump without repaired (C) which only 100,0%. Meanwhile though don't significant but clump repaired total (A) tend to to improve the culm diameter compared to the clump repaired apart (B) and or clump without repaired (C). Key words : bambu tali, Gigantochloa apus Kurz., clump damage, clump repairing, improve, culm productivity.